Effectiveness of a BOPPPS teaching in blood purification nursing within the context of resident teaching - Xia, Ningning; Liu, Jing; Wang, Hongying (Frontiers in Education, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of the Bridge-in, Objective, Pre-assessment, Participatory learning, Post-assessment, and Summary (BOPPPS) teaching model in improving educational outcomes within a blood purification nursing residency training program.BackgroundBOPPPS model is a structured, and learner-centered instructional framework that fosters active participation and self-directed learning. Despite its growing application in general education, its utility in specialized clinical nursing education remains insufficiently studied.MethodsA quasi-experimental design was used to facilitate sampling. A total of 118 undergraduate nursing students were included: 55 in the control group (2018–2019, traditional lecture-based teaching) and 63 in the intervention group (2020–2021, BOPPPS model). Data were collected using validated instruments, including the Academic Self-Efficacy Scale, the College Student Learning Engagement Scale, and the Learning Burnout Scale. In addition, final exam scores (scale of 0–100) and course satisfaction (17-item scale covering cognitive, skill-based, and emotional domains) were assessed. Statistical data analysis was conducted using SPSS 26.0, applying descriptive statistics, independent samples t-tests, and paired samples t-tests.ResultsCompared to the control group, students in the BOPPPS group reported significantly higher levels of academic self-efficacy and learning engagement, lower levels of learning burnout, improved examination performance, and greater course satisfaction (p < 0.05 or p < 0.01).ConclusionBOPPPS teaching model can significantly enhance cognitive, behavioral, and affective learning outcomes in the context of specialized clinical nursing education. This presents a promising pedagogical approach for residency training programs to optimize learner development while reduce academic burnout.